Ryegrass endophyte infection affects Argentine stem weevil adult behaviour and susceptibility to parasitism - Gerard, P.J. (New Zealand Plant Protection, 2000)
Pot experiments were undertaken to investigate whether Argentine stem weevil Listronotus bonariensis adults placed on endophyteinfected or endophytefree perennial ryegrass (Lolium perenne) exhibited behaviour differences that may lead to differing susceptibility to attack by the endoparasitoid Microctonus hyperodae There was no difference (P>005) in the behaviour of weevils on pots of Nui ryegrass infected with either the wildtype endophyte Neotyphodium lolii or AR1 a N lolii selection high in peramine but low in other key alkaloids Although adults were offered no choice over 60 of the adults were found off endophyteinfected plants during the observation period Weevils on high endophyte plants were found to spend less time in positions highly favourable for parasitoid oviposition (eg feeding P